Dead or alive - Clancy, Tom, 1947-; Blackwood, Grant (London : Penguin Books, 2011)
Jack Ryan, Jr. and his Campus colleagues John Clark and Ding Chavez, go after a vicious terrorist mastermind--the Emir--and they will bring him in ... dead or alive.
First published in the United States of America by G. P. Putnam's Sons 2010 and first published in Great Britain by Michael Joseph 2010.
Keywords: Ryan, jack (fictitious character) -- Fiction; Terrorism -- Prevention -- Fiction; Terrorists -- Fiction; Children of presidents -- Fiction; Intelligence officers -- Fiction; Fathers and sons -- Fiction